The Divine's Love Circle According to Muhyiddin Ibn Arabi - Naffaa, Rami (Jordan Journal of Social Sciences, 2021)
This research aims to show the nature of the relationship between the concept of Divine love in the approach of Mohiuddin Ibn Arabi, and its relationship to a number of other concepts such as creation, the rational being (mankind), affliction, and pain. Which is one of the pivotal concepts in the structure of Sheikh Al-Akbar who distinguishes between the three types of hearing, each of which is based on four components, and also distinguishes between three levels of love and their effect on the rational being that has in common the attributes and names that, in reality, belong to God originally, and how this is reflected on existence. This contributed to the formation of the Divine love circle, which as soon as a person approaches it, he becomes part of it and revolves in its orbit, as each point in it leads to the other in a continuous movement without stopping in order to return to the source. Divine love is considered a basic concept for understanding Ibn Arabi's system, as it made it a path of creation, a source of existence, a determinant of goals and a source of motives.